Penggunaan Berbagai Jenis Minyak Sebagai Sumber Energi Dalam Ransum Untuk Menurunkan Kadar Kolestrol Telur Puyuh (Cortunix-cortunix japonica) - Cut Aida Fitri; Zulfan Zulfan (Agricultural Faculty, 2007)
ABSTRACT. A study on the use vegetable oil as energy source in diet to decrease cholestrol concentration of quail egg conducted at exprimental Farm-Syiah Kuala University. The study was designed by Completely Randomized Design., divided into 5 treatments of vegetable oil source; soybean oil; coconut oil, palm oil, corn oil and zaitun oil. Result of present study showed that the difference in vegetable oil source in diet affected cholestrol concentration of quail diet. The use of palm or corn oil in quail diet has a more positive affect to decrease cholestrol concentration of quail egg. Corn oil in diet decrease 18.7 % cholesetrol and 23.8 % LDL compared to coconut oil. Differences in vegetable oil source in diet also significantly affected egg production but dit not affected body weight gain of quail.